A practical MOCVD approach to the growth of Pr1–xCaxMnO3 films on single crystal substrates. Issue 7 (11th June 2015) - Catalano, Maria R.; Toro, Roberta G.; Schilirò, Emanuela; Lo Nigro, Raffaella; Condorelli, Guglielmo G.; Malandrino, Graziella
<x xml:space="preserve">Abstract</x> Pr1–xCaxMnO3 thin films have been deposited through an insitu metal organic chemical vapor deposition (MOCVD) process using a molten multi‐metal source, consisting of the Pr(hfa)3·diglyme, Ca(hfa)2·tetraglyme, and Mn(tmhd)3 precursor mixture on single crystal substrates such as LaAlO3 (001) and MgO (001). Optimization of processing parameters has allowed the deposition of homogeneous thin films in morphology, composition, and thickness. The effect of substrate has been assessed in relation to structure and morphology.<inline-graphic xlink:href="ark:/27927/pgj1m9pm17j" content-type="pssa201532363-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> Field emission scanning electron microscope of a Pr0.7Ca0.3MnO3 film deposited at 1000 °C on MgO (001).